Word of Mouth and a Celebrity Endorsement to Improve Repurchase Intention - Prapanca, Detak; Febriansah, Rizky Eka; Rachmawati, Errina (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to determine the effect of Celebrity Endorser and Word Of Mouth on Repurchase Interest based on problems regarding competition related to repurchase intention with research objects in the Sidoarjo area. This study uses primary data with a quantitative approach. The sampling technique in this study used the purposive sampling method and the number of samples in this study were 116 respondents. This study used a data collection method using a questionnaire and equipped with a Likert scale measurement. The data analysis technique in this study used data analysis method using data instrument test (validity and reliability test), hypothesis testing using partial test (T), multiple correlation coefficient test (R) and multiple determination coefficient test (R2) by measuring through the SPSS statistical application program version 26). The results of this study indicate that Celebrity Endorser has a positive and significant effect on Repurchase Intention and Word of Mouth has a positive and significant effect on Repurchase Intention.